A comparative Study of Functional Outcomes for the Treatment of Arthrosis of the Knee Joint Using Platelet-Rich Plasma Injections After or Without Arthroscopy - علي, ناظم (Latakia University Journal -Medical Sciences Series, 2020)
The research provides a comparison between two methods for treating osteoarthritis. In the knee joint using platelet-rich plasma injections after or without arthroscopy, the study included 100 cases every fifty of them were treated in one way and the results were evaluated after surgery and the researcher reached the following results. Treatment with platelet-rich plasma injections after arthroscopy provided an advantage in terms of pain reduction and reduced joint effusion in the knee, improvement of the ability to rest on the limb (walking), and a marked reduction in the severity of symptoms and signs of degeneration was noted.